A B7‐CD28 family based signature demonstrates significantly different prognoses and tumor immune landscapes in lung adenocarcinoma. Issue 10 (17th September 2018) - Zheng, Shanbo; Luo, Xiaoyang; Dong, Chuanpeng; Zheng, Difan; Xie, Juntao; Zhuge, Lingdun; Sun, Yihua; Chen, Haiquan
Abstract : B7 family ligands and CD28 family receptors have complicated interaction for modulating immune functions. They play a central role in response to immunotherapy and outcome of patients with lung adenocarcinoma (LUAD). Thus, we analyzed B7‐CD28 family gene expression profiles in LUAD and generated a signature to predict prognosis and immune host status. B7‐CD28 family gene expression profiles and clinical data of LUAD from The Cancer Genome Atlas (TCGA) were analyzed. In the training cohort, prognostic association was assessed and then a prognostic signature was built with stepwise multivariable Cox analysis. The signature was validated by Kaplan–Meier and multivariable Cox analysis in several published gene expression datasets and a Fudan University cohort. Expression of immune cell populations and other immunotherapy predictors was further investigated. In TCGA LUAD cohort, eight B7‐CD28 family genes had prognostic association with p values <0.05. Stepwise regression generated a gene signature including two genes, CD28 and CD276. Signature high‐risk cases had worse overall survival (OS) and disease‐free survival (DFS) in three published gene expression datasets and a Fudan University validation cohort. The B7‐CD28 family based signature also significantly stratified OS and DFS in important clinical subsets, including stage I–II and EGFR mutant subsets. Signature high‐ and low‐risk tumor had significantly different expressions of PD‐L1 and tumor infiltrating leukocytes. The B7‐CD28 family based signature demonstrates significantly different prognoses and tumor immune landscapes in LUAD. Whether it could serve as potential biomarkers for immunotherapy needs further investigation. Abstract : What's new? Changes in the expression of immune‐modulating B7 ligands and CD28 receptors are associated with cancer. In particular, in lung adenocarcinoma, tumor‐cell expression of B7 and CD28 is associated with patient outcome. This study links eight B7‐CD28 family genes to lung adenocarcinoma prognosis. A B7‐CD28 gene signature was developed and validated in independent cohorts and clinical subsets. The signature was associated with predictive immune markers for immunotherapy, including PD‐L1 and tumor‐infiltrating lymphocytes. The prognostic signature potentially could be used to facilitate patient counseling and to stratify lung adenocarcinoma patients who may benefit from personalized immune checkpoint therapy.